UNIMAS Bus Schedule and Tracking Information System - Shamugam, Shankara Viknesh; Johari, Abdullah (Faculty of Computer Science and Information Technology, 2015)
Real time tracking is becoming more and more popular as devices utilizing the Global Positioning System (GPS) become more readily available. GPS is a fast-growing technology with potential application in many different industries. There are many uses for this device, from using it as map navigation to guiding cruise missiles to their target. In this paper, UNIMAS Bus Schedule and Tracking Information System is a system designed to show updated bus schedule, and to track real time location of the bus using GPS.